Conditionally Controlling Human TLR2 Activity via Trans-Cyclooctene Caged Ligands - van de Graaff, Michel J. (Bioconjug Chem, 2020)
[Image: see text] Toll-like receptors (TLRs) are key pathogen sensors of the immune system. Their activation results in the production of cytokines, chemokines, and costimulatory molecules that are crucial for innate and adaptive immune responses. In recent years, specific (sub)-cellular location and timing of TLR activation have emerged as parameters for defining the signaling outcome and magnitude. To study the subtlety of this signaling, we here report a new molecular tool to control the activation of TLR2 via “click-to-release”-chemistry. We conjugated a bioorthogonal trans-cyclooctene (TCO) protecting group via solid support to a critical position within a synthetic TLR2/6 ligand to render the compound unable to initiate signaling. The TCO-group could then be conditionally removed upon addition of a tetrazine, resulting in restored agonist activity and TLR2 activation. This approach was validated on RAW264.7 macrophages and various murine primary immune cells as well as human cell line systems, demonstrating that TCO-caging constitutes a versatile approach for generating chemically controllable TLR2 agonists.